2017
DOI: 10.1016/j.bbcan.2017.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Biological determinants of radioresistance and their remediation in pancreatic cancer

Abstract: Despite recent advances in radiotherapy, a majority of patients diagnosed with pancreatic cancer (PC) do not achieve objective responses due to the existence of intrinsic and acquired radioresistance. Identification of molecular mechanisms that compromise the efficacy of radiation therapy and targeting these pathways is paramount for improving radiation response in PC patients. In this review, we have summarized molecular mechanisms associated with the radio-resistant phenotype of PC. Briefly, we discuss the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 352 publications
(299 reference statements)
2
65
0
Order By: Relevance
“…Increasing evidence has suggested that cell proliferation, apoptosis, cell cycle progression, and DNA damage are associated with cell radiosensitivity. 24,25 As it was found out, CPNE1 expression levels were higher in radioresistant patients with TNBC than radiosensitive patients with TNBC, and the cell viability was also inhibited significantly in primary isolated TNBC cells with lower CPNE1 expression after radiation therapy. Measurement of γ-H2AX is a sensitive and specific assay for unrepaired DNA damages.…”
Section: Discussionmentioning
confidence: 93%
“…Increasing evidence has suggested that cell proliferation, apoptosis, cell cycle progression, and DNA damage are associated with cell radiosensitivity. 24,25 As it was found out, CPNE1 expression levels were higher in radioresistant patients with TNBC than radiosensitive patients with TNBC, and the cell viability was also inhibited significantly in primary isolated TNBC cells with lower CPNE1 expression after radiation therapy. Measurement of γ-H2AX is a sensitive and specific assay for unrepaired DNA damages.…”
Section: Discussionmentioning
confidence: 93%
“…In fact, only few guidelines and recommendations contain radiotherapy as a standard for primary care of PDA patients 18,19 . In addition to high treatment toxicities, this reluctance is due to intrinsic and acquired radioresistance which is commonly observed both in preclinical and clinical settings 2,20 . Mechanisms associated with the radioresistant phenotype of PDA include modifications in DNA damage response, DNA repair machinery and cell cycle checkpoint controls, as well as the hypoxic environment within the tumour and the activation of stellate cells leading to fibrosis 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Distinguishing of molecular mechanisms that diminish the efficacy of radiation therapy and targeting these pathways is important for improving radiation response in patients with pancreatic cancer [183]. In the study of Oonishi and colleagues, the proportion of Nucl Med Biomed Imaging, 2017 doi: 10.15761/NMBI.1000127 cancer stem-like CD44+/CD24+ cells was more enriched after X-ray irradiation compared to carbon ion irradiation.…”
Section: Discussionmentioning
confidence: 99%